2018
DOI: 10.1080/1343943x.2018.1530063
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maturity genes E2 and E3 on yield formation in soybean cultivar Enrei in warm region, Fukuyama in Japan

Abstract: Understanding how maturity genes affect soybean yield formation will provide important information for crop management decisions. This study aimed to reveal how maturity genes E2 and E3 in the soybean cultivar 'Enrei' affect yields and yield formation in warm regions of Japan. 'Enrei' (e2e3) and three near-isogenic lines of 'Enrei' (e2E3, E2e3, and E2E3) were cultivated in 2016 and 2017 in Fukuyama, Japan (34°30′N, 133°23′E). Two sowing dates were set in each year (June sowing and July sowing). E2 extended the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In this study, we found that E1 had some effect on soybean yield composition both on soybean pod formation was significant, and the effect of E2 and E3 genes on plant height of introduced soybeans was significant, and the effect of E2 was greater than that of E3 ( Table 4 ). Previous research has revealed that varieties carrying the E2/E3 combination can produce a greater number of main stems and flowers while maintaining a consistent pod set ratio, thereby resulting in increased pod production ( Kawasaki et al., 2018 ). We also found that E1 and E3 significantly affected the composition of soybean plant biomass, with E1 being the genetic locus that mainly affected the biomass of each component of soybean.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that E1 had some effect on soybean yield composition both on soybean pod formation was significant, and the effect of E2 and E3 genes on plant height of introduced soybeans was significant, and the effect of E2 was greater than that of E3 ( Table 4 ). Previous research has revealed that varieties carrying the E2/E3 combination can produce a greater number of main stems and flowers while maintaining a consistent pod set ratio, thereby resulting in increased pod production ( Kawasaki et al., 2018 ). We also found that E1 and E3 significantly affected the composition of soybean plant biomass, with E1 being the genetic locus that mainly affected the biomass of each component of soybean.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of GmGIa is suppressed in the e3e4 background or by the overexpression of GmCOL1a (Cao et al, 2015). A combination of E2 and E3 alleles can synergistically improve seed yield in July sowing in Japan (Kawasaki et al, 2018). Under long-day conditions, the expression of GmGIa oscillates following a circadian rhythm but is slightly out of sync with the expressions of the two GmFKF1 genes (Li et al, 2013), while under short-day conditions, the expression of GmGIa is dampened and no longer oscillates (Li et al, 2013).…”
Section: Gigantea Is a Big Target For Modification During Domesticatimentioning
confidence: 99%
“…A comprehensive understanding of maturity related genes and their influence on developmental stages, and genetic control have application in breeding and crop production. For example, an optimal placement of variety with the appropriate suite of maturity genes can help it reach the potential yield (Kawasaki et al 2018). In northern latitudes, yield is often limited by the narrower range in frost-free days that often forces farmers to delay planting to mitigate the risk of an early season frost killing, while a later planting can increase the chances of a late season frost that can kill plants prior to maturity (Halvorson et al 1995).…”
Section: Discussionmentioning
confidence: 99%